Women’s knowlegde and motivation concerning the papanicolaou test: subsidies for nursing practice - Moura, Ana Débora Assis; Silva, Synara Maria Gomes da; Farias, Leilane Martins; Feitoza, Aline Rodrigues (Rev Rene, 2010)
This study aims to describe the sociodemographic profi le of women attended at a health unit and investigate the knowledge and motivation which led them to be submitted to a Papanicolaou test. This is an exploratory-descriptive study of qualitative nature. Data collection was performed at a Center for Primary Health Care, in Paracuru – Ceará, through semi-structured interviews with fi fteen women. Collected data were grouped into four categories: knowledge; motivation; meaning; and feeling. The analysis showed that women considered it as kind of STD/AIDS test. The main motivation that led women to do the test was the presence of signs and symptoms. The examination also arises feelings of fear and shame. An urgent work is necessary to improve health education practices which make clear the senses and meanings of the test for the users.